Determinants of the Industrial Manufacturing Stock’s Holding Period (Journal of Islamic Economic Laws, 2018)
This study aims to identify the effect of Market Value (MV), Return on Asset (ROA), Earning per Share (EPS) and Bid-Ask Spread (BAS) over the holding period of manufacturing companies listed in Jakarta Islamic Index (JII). The data used here is period between 2014-2016. This research is a quantitative research. The data used in this research are the outstandingnumber of shares, the volume of stock transactions, closing price, ROA, and EPS. The technique for data analysis which will be used in this research is panel data regression test using REM model. The results of this study show that: 1). Market value have a significant positive effect on the manufacturing company stock’s holding period, which is shown by the value of sig t 0,0075. 2). ROA has no significant effect on on the manufacturing company stock’s holding period, which is shown by the value of sig t 0.1269. 3). EPS did not significantly affect the holding period of the manufacturing company's shares which was shown by the sig t value 0.7358. 4). The variable of Bid-Ask Spread does not significantly affect the holding period of the manufacturing company's stock which is shown by the value of sig t 0.1031. 5). MV, ROA, EPS, BAS according to test of model existence / F test is the existing model used with the value of F statistics 0.000397. 5). The value of Adjusted R2 of 19.85% indicates that variations in the variable of Holding Period can be explained by independent variables, and the remaining 80.65% of the variable of Holding Period are explained by other variables outside the research model.